Nanocable with thick active intermediate layer for stable and high-areal-capacity sodium storage. (December 2020) - Chen, Yijun; Yousaf, Muhammad; Wang, Yunsong; Wang, Zhipeng; Lou, Shuaifeng; Han, Ray P.S.; Yang, Yuan; Cao, Anyuan
Abstract: Developing electrodes cycling stably at high areal mass loadings is critical for sodium ion batteries (SIB) to reach practical applications, but remains challenging due to the larger ionic radius of Na + and generally sluggish electrochemical kinetics in thick electrodes. Consequently, most of the reported SIB electrodes exhibit low mass loadings (<1 mg cm −2 ) and thereby limited areal capacities. Here, we develop a hybrid network structure with orthorhombic Nb2 O5 coatings sandwiched between three-dimensional carbon nanotube (CNT) underlayers and outer carbon shells. By thickening Nb2 O5 intermediate layers, we can effectively raise the mass loadings of the sponge anodes with the electron and ion transport kinetics well maintained, owing to the highly conductive CNT substrate, porous network and carbon shell-enabled robust nanocable structures. As a result, the sponge anodes exhibit reversible areal capacities of 2.7 mAh cm −2 after 200 cycles at mass loadings up to 16.6 mg cm −2, exceeding 9 times those of previous Nb2 O5 -based structures, and the achieved cycling stability is also among the best of the high-areal-capacity SIB anodes reported so far. Our work shows that thickening intermediate active coatings in rationally designed nanocable structures represents an effective way to promote their areal sodium storage performance for practical use. Graphical abstract: Image 1 Highlights: Three-dimensional network structured electrode composed of interconnected nanocables. Nanocable comprises carbon nanotube core, Nb2 O5 intermediate layer and carbon shell. Thickening intermediate layer to raise electrodes mass loadings and areal capacities. Robust hierarchical structure enables stable cycling performance for sodium storage.